Influence of joint fissure occurrence on stress distribution of coal wall in large mining height - Weibin Guo; Yichen Gao; Gang Wang (Scientific Reports)
Abstract In order to ensure the stability of coal wall of fully mechanized mining face with large mining height, Aiming at the prominent problem that the rib spalling rate of coal wall in fully mechanized mining face with large mining height is high and is significantly affected by joint cracks, this paper comprehensively uses theoretical analysis, numerical simulation and other research methods to explore the damage effect of joint cracks on coal wall, and obtains the influence law of joint surface occurrence on abutment pressure in limit equilibrium area. Based on the stability theory of coal wall pressure bar, the expression function of abutment pressure distribution in the limit equilibrium zone of large mining height working face is constructed. The research shows that under the condition of large mining height working face, with the increase of joint plane dip angle, the damage of coal shows a trend of increase–decrease–increase, and the abutment pressure at the same position in the limit equilibrium zone shows a trend of decrease–increase–decrease. Under certain conditions, with the increase of the azimuth angle of the joint surface, the damage of the coal decreases first and then increases. The bearing pressure at the same position in the limit equilibrium zone increases first and then decreases. With the increase of joint plane spacing, the number of joint planes gradually decreases, and the damage of coal shows a decreasing trend. The abutment pressure at the same position in the limit equilibrium zone increases. The dip angle and azimuth angle of the joint surface have a relatively small influence on the bearing pressure in the limit equilibrium zone.